The Paper Trade in Early Modern Europe
1 online resource.
Keywords: "This book attends to the most essential, lucrative, and overlooked business activity of early modern Europe: the trade of paper. Despite the well-known fact that paper was crucial to the success of printing and record-keeping alike, paper remains one of the least studied areas of early modern history. Organised into three sections, 'Hotspots and Trade Routes', 'Usual Dealings', and 'Recycling Economies', the chapters in the collection shed light on the practices, materials, and networks of the paper trade. Altogether, the collection uncovers the actors involved in the networks of paper production, transportation, purchase, and reuse, between the thirteenth and nineteenth centuries and across the central and peripheral papermaking regions of Europe"--